2021
DOI: 10.13189/ujaf.2021.090305
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Analysis of Financial Literacy Level in Azerbaijan

Abstract: Financial literacy is knowledge that every person needs in everyday life. Studying theory, mastering practical skills, developing financial thinking -all this will allow each of us to become financially successful. Research Objective: The aim of this study is to ascertain the financial literacy level of individuals living in Baku, The Republic of Azerbaijan. 280 people between the ages of 17-60 were involved in the survey, comprised of public and private sector employees, self-employed, retirees and students t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…These factors can be gender difference, access to education, ethnicity, personal finance, lack of trust in financial institutions, distance and lack of proper guidance. A few of these hindrances were also corroborated by earlier researchers [32]. Further exploratory studies on the topic can be undertaken related to gender, ethnicity and trust with financial inclusion and literacy.…”
Section: Findings and Conclusionsupporting
confidence: 72%
See 1 more Smart Citation
“…These factors can be gender difference, access to education, ethnicity, personal finance, lack of trust in financial institutions, distance and lack of proper guidance. A few of these hindrances were also corroborated by earlier researchers [32]. Further exploratory studies on the topic can be undertaken related to gender, ethnicity and trust with financial inclusion and literacy.…”
Section: Findings and Conclusionsupporting
confidence: 72%
“…Education is considered as one of the factors in determining whether one is financially literate or not. In a study in the Republic of Azerbaijan, it was found that Financial Literacy differs based on demographic factors such as gender, age, marital status, income, profession and education level [32]. Women who are single with low education levels are considered in the vulnerable group.…”
Section: Financial Literacymentioning
confidence: 99%
“…Socio-demographic Indicators and Retirement Preparedness Financial planning behaviour including retirement preparedness has been investigated in the past and was found to be influenced by a myriad of factors including socio-demographics such as age, gender, ethnicity, marital status, education level, income level, number of children, household income, and many more (Tamborini & Purcell, 2016;Zhou & Chou, 2018;Kumar, Tomar & Verma, 2019;Chun, Fenn & Al-Khaled, 2021;Akbulaev & Mammadova, 2021). Therefore, selected socio-demographic variables, household size, and income adequacy are included in this study and the following are proposed: H5: There is a significant positive relationship between household size and retirement preparedness among Malaysian female millennials.…”
Section: 6mentioning
confidence: 99%
“…Section A contains information on the demographic profile of the respondents including gender, age, ethnicity, marital status, household size and current income adequacy. These demographic characteristics were previously found to have associations with various financial planning behaviour such as retirement planning [15,37] and therefore were controlled in the study. Section B consisted of information on financial literacy level (FLL) adopted from [38].…”
Section: Research Instrumentmentioning
confidence: 99%